Binding of the Second Generation Non-nucleoside Inhibitor S-1153 to HIV-1 Reverse Transcriptase Involves Extensive Main Chain Hydrogen Bonding - Jingshan Ren; Charles E. Nichols; Louise E. Bird; Tamio Fujiwara; Hirohiko Sugimoto; David I. Stuart; D.K. Stammers (2000)
S-1153 (AG1549) is perhaps the most promising non-nucleoside inhibitor of HIV-1 reverse transcriptase currently under development as a potential anti-AIDS drug, because it has a favorable profile of resilience to many drug resistance mutations. We have determined the crystal structure of S-1153 in a complex with HIV-1 reverse transcriptase. The complex possesses some novel features, including an extensive network of hydrogen bonds involving the main chain of residues 101, 103, and 236 of the p66 reverse transcriptase subunit. Such interactions are unlikely to be disrupted by side chain mutations. The reverse transcriptase/S-1153 complex suggests different ways in which resilience to mutations in the non-nucleoside inhibitors of reverse transcriptase binding site can be achieved.